Picosecond‐resolved X‐ray absorption spectroscopy at low signal contrast using a hard X‐ray streak camera. (24th June 2015) - Adams, Bernhard W.; Rose‐Petruck, Christoph; Jiao, Yishuo
<x xml:space="preserve">Abstract</x> A picosecond‐resolving hard‐X‐ray streak camera has been in operation for several years at Sector 7 of the Advanced Photon Source (APS). Several upgrades have been implemented over the past few years to optimize integration into the beamline, reduce the timing jitter, and improve the signal‐to‐noise ratio. These include the development of X‐ray optics for focusing the X‐rays into the sample and the entrance slit of the streak camera, and measures to minimize the amount of laser light needed to generate the deflection‐voltage ramp. For the latter, the photoconductive switch generating the deflection ramp was replaced with microwave power electronics. With these, the streak camera operates routinely at 88 MHz repetition rate, thus making it compatible with all of the APS fill patterns including use of all the X‐rays in the 324‐bunch mode. Sample data are shown to demonstrate the performance.